Experiences of those taking part in the BeeZee Bodies family-based weight management intervention: a qualitative evaluation - Edmunds, L; Rennie, K; King, S; Mayhew, H (Lifescience Global, 2014)
The need for effective community, child weight management interventions continues. The BeeZee Bodies (BZB) family-based child weight management programme for 7-11-year-olds and 12-15–year-olds has been developed iteratively over five years, with quantitative and qualitative evaluations refining the programmes. The aim of this study was to present the experiences and opinions of those taking part in BZB programmes as part of a real world evaluation. Three focus groups, following a semi-structured protocol, were conducted with 20 participants (15 parents, 5 adolescents) 3 months post-intervention. Analyses were thematic, iterative and underpinned by Grounded Theory. Two themes emerged; (1) programme contents, (2) social interactions, with each sub-divided. Parents described increased appreciation of physical activity and dietary components, improvements in parenting and good relationships with personnel. A wide range of positive personal outcomes and changes within the family were perceived by parents and adolescents including: changes in physical activity take-up, eating habits, portion sizes, and an improved understanding of parenting an overweight child. The parenting skills element further enhanced the social cohesion fostered through attendance. There were opportunities to build new friendships for both parents and adolescents, and for parents to interact with their offspring in a different context, all of which supported behaviour change. The BZB programme was viewed by participants as successful and delivered by engaging personnel. Key strengths were social cohesion generated by including parenting sessions and inclusiveness of the physical activities on offer. BZB has been refined in response to qualitative evaluations and reviews and this process continues.